Hematopoietic progenitors are required for proper development of coronary vasculature. (September 2015) - Lluri, Gentian; Huang, Vincent; Touma, Marlin; Liu, Xiaoqian; Harmon, Andrew W.; Nakano, Atsushi
Abstract: Rationale: During embryogenesis, hematopoietic cells appear in the myocardium prior to the initiation of coronary formation. However, their role is unknown. Objective: Here we investigate whether pre-existing hematopoietic cells are required for the formation of coronary vasculature. Methods and results: As a model of for hematopoietic cell deficient animals, we used Runx1 knockout embryos and Vav1-cre ; R26-DTA embryos, latter of which genetically ablates 2/3 of CD45 + hematopoietic cells. Both Runx1 knockout embryos and Vav1-cre ; R26-DTA embryos revealed disorganized, hypoplastic microvasculature of coronary vessels on section and whole-mount stainings. Furthermore, coronary explant experiments showed that the mouse heart explants from Runx1 and Vav1-cre ; R26-DTA embryos exhibited impaired coronary formation ex vivo. Interestingly, in both models it appears that epicardial to mesenchymal transition is adversely affected in the absence of hematopoietic progenitors. Conclusion: Hematopoietic cells are not merely passively transported via coronary vessel, but substantially involved in the induction of the coronary growth. Our findings suggest a novel mechanism of coronary growth. Highlights: We studied the role of hematopoietic progenitor cells on the coronary development. Mice lacking hematopoietic progenitor cells have hypoplastic coronary vessels. These cells are not merely passengers, but substantially involved in coronary growth.